Comparative Analysis of Skill Shortages, Skill Mismatches, and the Threats of Migration in Labor Markets: A Sectoral Approach in North Macedonia, Türkiye, Ethiopia, and Ukraine - Cvetkoska, Violeta; Trpeski, Predrag; Ivanovski, Igor; Peovski, Filip; İmrol, Meryem Hamsi; Babadoğan, Berk; Ecer, Halil; Görür, Durmuş Ziya; Selvi, Umut; Hunde, Adula Bekele; Gemeda, Fekede Tuli; Dubi, Yosef Beco; et al. (MDPI AG, 2025)
Labor markets worldwide are increasingly strained by skill shortages, mismatches, and migration pressures, disrupting workforce stability and economic growth. This study conducts a comparative sectoral analysis in North Macedonia, Türkiye, Ethiopia, and Ukraine, focusing on the manufacturing, information and communication technology, and hospitality sectors, to examine the root causes and economic consequences of these challenges. Using a qualitatively driven mixed-methods approach, the research integrates expert interviews, surveys, and labor market data to assess skill gaps, workforce imbalances, and the role of migration. The findings reveal education–industry misalignment, inadequate vocational training, and low wages as persistent drivers of shortages. Additionally, the war in Ukraine, internal conflicts in Ethiopia, and refugee inflows in Türkiye amplify workforce instability, while North Macedonia faces severe emigration, particularly in the sectors of manufacturing and information and communication technologies. These insights are essential for policymakers, industry leaders, and educators in designing labor market interventions that foster workforce resilience. The study recommends national qualification reforms, industry–education collaboration, and improved wage structures to mitigate talent loss and strengthen labor market sustainability. By offering empirical evidence from diverse socio-economic contexts, this research contributes to global discussions on workforce development, migration economics, and labor policy reforms.
Keywords: skill shortage; skill mismatch; labor migration; sectoral analysis; talent retention